The impact of sovereign credit rating changes on financial market returns in Africa - Mutize, Misheck (Graduate School of Business (GSB), 2019)
In both developed and developing countries, the extent to which sovereign credit rating announcements bridge the information gap between investors and issuers of securities is debatable. Thus, this thesis investigates the effects of the information provided by credit rating agencies on financial markets in 30 African countries during the period of 1994 to 2014 in order to determine whether long-term foreign currency sovereign credit rating announcements contain material information that influences the secondary market stock and bond returns. The analyses draws the following findings. First, African financial markets are weakly sensitive to sovereign credit rating announcements, which implies that there is no significant evidence of excess market returns influenced by sovereign credit rating announcements. Hence, it is inferred that the announcements of sovereign credit ratings do not significantly change the African financial market returns because they are already perceived to be risky markets, and thus attract mostly passive and long-term investors. Second, the changes in sovereign ratings do not have the same implications for both stockholders and bondholders as shown by the weak positive association between sovereign credit ratings and stock and bond markets. Third, there are marginal regional sovereign rating spillover impacts that are quickly absorbed into capital markets trading long-term securities. However, there are marginal spillover effects that persist over longer time periods in sovereign ratings of countries in the same region from a sovereign rating change in a neighbouring country. These results imply that the regional bilateral linkages between countries serve as channels of capital and sovereign credit rating information flow. Lastly, the sovereign credit ratings do not significantly impact bond market efficiency. In contrast, stock markets show evidence of weak form efficiency implying that long-term sovereign credit ratings positively affect equity market efficiency in Africa. Thus, the empirical findings in this thesis show that the operations of credit rating agencies and their sovereign credit ratings appear to be less important in the operation of stocks and bond markets in Africa. Governments should however take cognizance of the long-term information exchange between investors and borrowers, and the consequential nature of credit ratings to proactively manage the risks of negative sovereign credit rating announcements.